Transcriptomic and Proteomic Tools in the Study of Hg Toxicity: What Is Missing? - Oliveira, Cláudia S.; Segatto, Ana L. A.; Nogara, Pablo A.; Piccoli, Bruna C.; Loreto, Élgion L. S.; Aschner, Michael; Rocha, João B. T. (Frontiers in Genetics, 2020)
Mercury is a hazardous substance that has unique neurodevelopmental toxic effects in humans. However, the precise sequence of molecular events that culminate in Hg-induced neuropathology is still unknown. Though the omics studies have been generating an enormous amount of new data about Hg toxicity, our ability to interpret such a large quantity of information is still limited. In this opinion article, we will reinforce the necessity of new high throughput and accurate analytical proteomic methodologies, especially, thiol and selenol-proteome. Overall, we posit that improvements in thiol- and selenol-proteomic analyses will be pivotal in identifying the primary cellular targets of Hg. However, a better understanding of the complex cascades and molecular pathways involved in its toxicity will require extensive complementary studies in more complex systems.